Self-efficacy as a Predictor of Self-Management Capacity in Cancer Patients: Efikasi Diri sebagai Prediktor Kapasitas Manajemen Diri pada Pasien Kanker - Zahraa Abbass (Universitas Muhammadiyah Sidoarjo, 2024)
Background: Self-efficacy, a fundamental concept in psychology, reflects an individual’s confidence in their ability to accomplish specific tasks and achieve goals. It significantly influences cancer patients' coping mechanisms, treatment adherence, psychological distress management, and overall well-being. Specific Background: While existing literature highlights various aspects of self-efficacy among cancer patients, few studies comprehensively address the relationship between self-efficacy and socio-demographic variables. Knowledge Gap: There remains a paucity of research examining the interaction between self-efficacy and demographic characteristics such as age, gender, and educational attainment among cancer patients. Aims: This study aims to assess the level of self-efficacy in cancer patients and explore its correlation with socio-demographic characteristics. Results: A cross-sectional descriptive design was employed with a purposive sample of 107 cancer patients. The findings revealed that 83% of participants exhibited a high level of self-efficacy, while only 6.50% demonstrated low self-efficacy. A statistically significant association was identified between age and self-efficacy levels (P-value = 0.000). Novelty: This research is among the first to highlight the influence of age and chronic illness on self-efficacy in cancer patients while showing no significant relationships with gender, education, or social status. Implications: The study underscores the importance of promoting self-efficacy in cancer care, particularly through targeted interventions that consider age and chronic disease status. Enhancing self-efficacy can improve treatment adherence and psychological adjustment, thereby positively impacting the overall health outcomes of cancer patients. Highlights: 83% of cancer patients had high self-efficacy levels. Age significantly correlates with self-efficacy (P-value = 0.000). Self-efficacy unaffected by gender, education, or social status. Keywords: self-efficacy, cancer patients, socio-demographic characteristics, treatment adherence, psychological well-being